P–493 Couples joint narratives of coping with and making sense of recurrent pregnancy loss: a dyadic interview study. (6th August 2021) - Koert, E; Nielsen, H S; Schmidt, L
Abstract: Study question: What are couples' joint narratives of coping with, and making sense of recurrent pregnancy loss? Summary answer: Couples can become stuck in patterns of communication and coping roles that may be dissatisfying and not reflect the complexity of their experience of RPL. What is known already: Fertility problems such as recurrent pregnancy loss (RPL) are unique health issues because they are a couple problem, in that they involve a blocked parenthood goal for both members of the couple regardless of the cause or source of the fertility issue. Previous research has focused on the psychosocial impact on the individual or examined gender differences in men and women's response to RPL. Research suggests that couples' relationships are impacted, but few examine this issue in interviews with couples as participants. We need appropriate study designs to examine and understand the couple's experience and process on a dyadic level. Study design, size, duration: This was a qualitative study using dyadic interviews and analysis. This method facilitates a co-construction of meaning and joint narrative between couples through sharing and comparing their experience in a conjoint dyadic interview. Thirteen couples who were referred to the RPL program, in Rigshospitalet, Copenhagen, Denmark were interviewed over a two-month period in 2017–2018. Interviews were held at Rigshospitalet and ranged between 81 and 109 minutes (average 91 minutes). Participants/materials, setting, methods: Inclusion criteria included: heterosexual couples with at least three pregnancy losses (PL) under 12 weeks gestation with no children/one child and willing to be interviewed in English. Thirty invitations were sent to couples who met the inclusion criteria and 15 couples contacted the interviewer to schedule an interview. Semi-structured dyadic interviews were conducted in person with 13 couples. Data was analyzed using dyadic analysis with a focus on common themes in co-constructed meaning across couples. Main results and the role of chance: On average, participants had been in their relationship for 8.4 years, experienced three PLs (range three–six), with most recent PL occurring 4.3 months before the interview. Couples described becoming stuck in patterns of communication and in rigid roles of coping and relating (e.g., the optimist, the emotional one) that could be dissatisfying and not meet their needs and not reflect the nuances and complexity of their experience of RPL. Common roles included the "optimist" versus the "pessimist", the "talker" versus the "listener" and the "emotional" versus the "rational / problem solver". While these roles were rooted in some truth of their experience, the rigidity of these roles did not create space and flexibility for the full spectrum of their reactions and experience. For example, a woman said, "I hope for him to be the pessimist so I get to be the optimist sometimes" and several men shared the depth of their grief for the first time. The interviews were a way to highlight and create a new dynamic by allowing couples to respond to and correct their partner's assumptions about their experience or role (e.g., "that's not how I feel all the time") and try new ways of communicating. Limitations, reasons for caution: The findings cannot be generalized to all couples who have experienced RPL given the study design. Whilst dyadic interviews allow for a fuller, more nuanced narrative account, couples may omit some of their experience in the interview due to social desirability. Wider implications of the findings: This study provides a better understanding of the complexity of communication patterns and roles in couples with RPL that can improve provision of support and counselling. Dyadic interviews can provide opportunities for couples to communicate differently and break out of dissatisfying patterns while creating common ground and generating shared meaning. Trial registration number: N/A